EFEKTIFITAS PENGGUNAAN MEDIA KOMUNIKASI DALAM RANGKA SOSIALISASI PROGRAM GPMB (GERAKAN PEMBINAAN MASYARAKAT BACA) DI JAWA BARAT: Tine Silvana R ,H. Rohanda - Jurnal COMMED (Commed : Jurnal Komunikasi dan Media, 2017)
This research explore efectivity of media uses for GPMB’s (Gerakan Pembinaan Masyarakat Baca) programat jawa Barat. This research aim to explore attractiveness of message, content of information, and obstaclesof media communication at socialization of GPMB’s program in Jawa Barat. The research method’s isqualitative descriptivvw which explain the fact sistematicly ang has specific population characteristicscarefully. The data collected by interview 8 leader of library as coach of GPMB, observation to road show atCiamis, Bogor and Karawang. The result of this research show content of information use manual book,brochure, news paper and billboard was completed about this program. The format of content of informationwas easy to understanded. The obstacles from delivery message was lack of interested for read. The efectiveway to delivery the message was from roadshow but they cann’t delivery all of content information to all oftarget information. This research suggest “Bapusipda” will guide and give media information routinely toall library at Jawa BaratEfectivity of media communication, socialization, Gerakan Pembinaan Masyarakat Baca